2011
DOI: 10.1093/cercor/bhr049
|View full text |Cite
|
Sign up to set email alerts
|

Fake or Fantasy: Rapid Dissociation between Strategic Content Monitoring and Reality Filtering in Human Memory

Abstract: Memory verification is crucial for meaningful behavior. Orbitofrontal damage may impair verification and induce confabulation and inappropriate acts. The strategic retrieval account explains this state by deficient monitoring of memories' precise content, whereas the reality filter hypothesis explains it by a failure of an orbitofrontal mechanism suppressing the interference of memories that do not pertain to reality. The distinctiveness of these mechanisms has recently been questioned. Here, we juxtaposed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
42
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(54 citation statements)
references
References 48 publications
11
42
1
Order By: Relevance
“…These are the stimuli on which reality confusing patients, who produced confabulations and were disoriented, failed; they had a specific increase of false positives in response to Dis2 stimuli (Nahum et al, 2012;Schnider, Ptak, et al, 2000;Schnider & Ptak, 1999;Schnider et al, 1996aSchnider et al, , 1996b. Processing of these stimuli activated the posterior medial orbitofronal cortex (Schnider, Treyer, et al, 2000) and induced a specific frontal positivity at 200-300 msec in previous evoked potential studies ( Wahlen et al, 2011;Schnider et al, 2002).…”
Section: Main Stimuli Of Interestmentioning
confidence: 67%
See 3 more Smart Citations
“…These are the stimuli on which reality confusing patients, who produced confabulations and were disoriented, failed; they had a specific increase of false positives in response to Dis2 stimuli (Nahum et al, 2012;Schnider, Ptak, et al, 2000;Schnider & Ptak, 1999;Schnider et al, 1996aSchnider et al, , 1996b. Processing of these stimuli activated the posterior medial orbitofronal cortex (Schnider, Treyer, et al, 2000) and induced a specific frontal positivity at 200-300 msec in previous evoked potential studies ( Wahlen et al, 2011;Schnider et al, 2002).…”
Section: Main Stimuli Of Interestmentioning
confidence: 67%
“…Previous studies have shown that reality filtering and recognition effects can be seized over frontal, central, and posterior electrode sites (Wahlen et al, 2011;Schnider et al, 2002), but that the precise optimal electrode position may vary. We, therefore, grouped electrodes into ROIs for the analysis: frontal, central, and posterior ROIs (as in the previous studies), to which we added a central right and central left ROIs.…”
Section: Waveform Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown that this process is rapid (200-300 ms after stimulus presentation; Schnider, Valenza, Morand, & Michel, 2002), and that it dissociates from other memory control processes like context source memory (BouzerdaWahlen, Nahum, Liverani, Guggisberg, & Schnider, 2014;Johnson, Kounios, & Nolde, 1997;Mitchell & Johnson, 2009), strategic retrieval monitoring (BouzerdaWahlen, Nahum, Ptak, & Schnider, 2013;Gilboa et al, 2006;Wahlen, Nahum, Gabriel, & Schnider, 2011) and temporal order memory (Liverani et al, 2015). These processes are laborious and have different signatures in evoked potential studies (Bouzerda-Wahlen et al, 2014;Liverani et al, 2015;Wahlen et al, 2011). Orbitofrontal reality filtering is also different from reality monitoring, the ability to distinguish between the memory of a thought and a memory of a perception experienced in the past (Johnson & Raye, 1981).…”
mentioning
confidence: 99%